E-Learning For Kids Education About Corona Virus Pada Sdn 01 Duren Tiga - Juninisvianty, Tri; Saputri, Daniati Uki Eka; Khasanah, Nurul; Riyanto, Eko Arif; Dwi, F Lia; Seimahuira, Syarah; Salim, Agus; Rosiyadi, Didi (Indonesian Journal on Software Engineering (IJSE), 2020)
Abstract: E-Learning For Kids Education about Corona Virus (EduCovid-19) is an e-learning website for elementary school students to be able to bridge teachers, parents and students in providing correct information about the spread, danger, and handling of corona virus outbreaks. In addition, this website is equipped with Thematic material that students get at school. By implementing a primary school curriculum for thematic lessons, it is hoped that it can adjust the learning system that is available in schools. The design of EduCovid-19 contains material in the form of education and exercises about Covid-19 and thematic lessons where in one of these materials there will be questions and answers as one of the interactive assessment methods for teachers. The method used in the design of this system is RAD and the research methods used in data collection are interviews, observation and case studies. By applying the learning system using EduCovid-19, it will be able to increase children's interest in the learning process that is currently underway, namely school from home and provide students with knowledge about the dangers and ways to overcome Covid-19.Keywords: Elearning, School, Covid-19, EduCovid-19Abstrak: E-Learning For Kids Education about Corona Virus (EduCovid-19) merupakan website elearning bagi pelajar sekolah dasar untuk dapat menjembatani guru, orang tua dan siswa dalam memberikan informasi yang benar seputar penyebaran, bahaya, dan penangan terkait wabah virus corona. Selain itu, di website ini dilengkapi dengan materi Tematik yang siswa dapatkan di sekolah. Dengan menerapkan kurikulum sekolah dasar pelajaran tematik, diharapkan dapat menyesuaikan sistem pembelajaran yang terdapat di sekolah. Perancangan EduCovid-19 ini berisi materi-materi berupa edukasi serta latihan soal seputar Covid-19 dan pelajaran tematik dimana dalam salah satu materi tersebut akan ada tanya jawab sebagai salah satu metode penilaian interaktif bagi para guru. Dalam perancangan sistem ini menggunakan metode RAD dan metode penelitian yang digunakan dalam pengumpulan data yaitu wawancara, observasi dan studi kasus. Dengan penerapan sistem pembelajaran menggunakan EduCovid-19 nantinya mampu meningkatkan ketertarikan anak dalam proses pembelajaran yang saat ini sedang berlangsung yaitu school from home dan memberikan pengetahuan kepada siswa mengenai bahaya dan cara menghindari serta mengatasi Covid-19.Kata kunci: Elearning, Sekolah, Covid-19, EduCovid-19